Pengaruh Manajemen Kurikulum Terhadap Prestasi Belajar Siswa Kelas XI IPA Di MA Unggulan Mamba’ul Huda Krasak Tegalsari Banyuwangi - Sumari Mawardi; M. Zainul Ihsan Mustofa (Institut Agama Islam Darussalam Blokagung, 2020)
The objectives of this research are 1). Knowing How Curriculum Management in MA Featured Mamba'ul Huda Krasak Tegalsari Banyuwangi, 2). Knowing How Students' Achievement In Ma Unggulan Mamba'ul Huda Krasak Tegalsari Banyuwangi, 3). Knowing Is There The Effect Of Curriculum Management On Students' Learning Presence in MA Unggul Mamba'ul Huda Krasak Tegalsari Banyuwangi, 4). Knowing How Much Influence Curriculum Management Has On Students' Learning Presence in MA Unggals Mamba'ul Huda Krasak Tegalsari. This type of research is descriptive quantitative by using the method of observation, interview, questionnaire, and documentation for data collection techniques while the analysis uses the correlation of Poduct Moment. The population of this research is Class XI at MA Featured Mamba'ul Huda Krasak Tegalsari as the sample Class XI IPA with 37 respondents. After conducting an analysis of his insights, it was found that the management of the curriculum at MA Unggul Huda Krasak Tegalsari was classified as good and student achievement was also classified as good. The existence of influence of curriculum management on student learning preservation at MA Featured Mamba'ul Huda Krasak Tegalsari and the influence is 77% while the rest is 23% by other variables.